Analisis Pengaruh Dimensi Budaya Terhadap Penggunaan Aplikasi Trasnportasi Online Menggunakan UTAUT2 dan Budaya Hofstede - Thofik Nugroho; Wing Wahyu Winarno; Kholid Haryono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
It is important for online transportation application company to know the factors that influence the use of online transportation applications. Culture is an important factor in research into the acceptance of technology use. This study uses the UTAUT2 research model and Hofstede's cultural dimensions. The main objective of this research will be to investigate that culture influences users in using online transportation applications. The measurement method uses PLS SEM. It is proven that culture influences the use of online transportation applications. It is proven that by adding the cultural dimension in the UTAUT2 model, it can better explain the behavior of using online transportation applications